Gondwanan perspectives: Theropod dinosaurs from western gondwana. A brief historical overview on the research of mesozoic theropods in Gondwana - Ezcurra, Martin Daniel (2017)
THE study of Gondwanan non-avian theropods has beenoutstandingly prolific in the last three decades and hasshown that the taxonomic and morphological diversity ofthe group is comparable to that of Laurasia. The MesozoicGondwanan neotheropod record is currently composed ofcoelophysoids, basal averostrans, ceratosaurids, abelisauroids,megalosauroids, carcharodontosaurids, megaraptorans,basal coelurosaurs, compsognathids, alvarezsauroids,unenlagiids, and basal avialans, as well as putativetyrannosauroids, ornithomimosaur-like forms, andtroodontids (Novas, 2009; Benson et al., 2012). As a consequenceof this diversity, the Gondwanan non-avian theropodrecord has been crucial to understand the evolutionand global biogeography of dinosaurs during the Mesozoic.The contributions of this special issue of Ameghinianaenrich the record of some poorly known Gondwanan theropodclades with the description of four new species: twoTriassic coelophysoids, a Jurassic basal tetanuran, and aCretaceous ornithomimosaurian. In addition, in this issue itis described for the first time the cranial endocast of amegaraptoran and the forelimb posture of the enigmatictheropod Chilesaurus.